Occupational experiences and their importance for young peoples’ mental health - Ingvill Sørensen Drevland; Mona Asbjørnslett; Unni Sveen; Karen Synne Groven (Scandinavian Journal of Occupational Therapy)
Background Young peoples’ mental health challenges have increased in recent years to become an urgent public health issue. Research is required to gain a better understanding of how occupations influence young peoples’ everyday lives and support their mental health.Aim How do young people experience engaging in various occupations in their daily lives, and how do these experiences shape their mental health?Method Semi-structured interviews were conducted with 12 Norwegian young people aged 13–16 years. Verbatim transcriptions of the interviews were analysed using thematic analysis.Results Four core themes emerged: ‘doing’ for balance and stability; self-discovery through doing; intentional doing to recharge and feel free; and reflecting on the consequences of doing social media.Conclusions Young peoples’ occupational experiences shape their mental health in several ways: they serve as coping strategies, as a means to experience joy and accomplishment, and as a source of routines and opportunities for relaxation. We suggest that health-promoting initiatives for young people would strongly benefit from the inclusion of an occupational perspective.